2013
DOI: 10.1037/a0033851
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate does not influence smoking-reinforced responding or attentional performance in adult smokers with and without attention deficit hyperactivity disorder (ADHD).

Abstract: Individuals with Attention Deficit Hyperactivity Disorder (ADHD) smoke cigarettes at rates higher than the general population and questions have been raised about how stimulant drugs – the frontline pharmacological treatment for ADHD – influence smoking risk and behavior in those with ADHD. In the present study adult regular smokers with (n=16) and without (n=17) ADHD participated in 3 experimental sessions in which they completed a Progressive Ratio (PR) task to measure the relative reinforcing effects of cig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…[34][35][36][37][38][39][40] Although clinical trials of treatmentseeking smokers with ADHD have shown that neither methylphenidate nor amphetamine increase smoking, 41,42 studies have not examined how stimulant treatment might influence naturalistic smoking among individuals with ADHD who are not trying to quit. Such studies are necessary to resolve this discrepancy between laboratory studies and clinical trials of smoking cessation.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36][37][38][39][40] Although clinical trials of treatmentseeking smokers with ADHD have shown that neither methylphenidate nor amphetamine increase smoking, 41,42 studies have not examined how stimulant treatment might influence naturalistic smoking among individuals with ADHD who are not trying to quit. Such studies are necessary to resolve this discrepancy between laboratory studies and clinical trials of smoking cessation.…”
Section: Limitationsmentioning
confidence: 99%
“…[34][35][36][37][38][39] In contrast, however, a recent study revealed no effect of methylphenidate on choices of cigarette puffs versus money for ADHD and non-ADHD adults. 40 Randomized clinical trials of stimulants to aid cessation among ADHD smokers have revealed no evidence that either methylphenidate or amphetamine products are more effective than placebo for facilitating smoking abstinence. 41,42 However, in contrast to some laboratory studies, both stimulant and placebotreated individuals in these studies reduced the number of cigarettes smoked daily, 42,43 and 1 open label study revealed that methylphenidate treatment decreased smoking to below the population rate.…”
mentioning
confidence: 99%